2022
DOI: 10.1200/jco.22.00488
|View full text |Cite
|
Sign up to set email alerts
|

Do Female BRCA2 Pathogenic Variant Carriers Have an Increased Risk of Lung Cancer?

Abstract: Li et al 1 recently reported the association between risk of 22 cancers and BRCA1 and BRCA2 pathogenic variants (PVs) in the Consortium of Investigators of Modifiers of the BRCA1/2 cohort. Among 3,184 BRCA1 and 2,157 BRCA2 families, BRCA1 and BRCA2 PVs were associated with an increased risk of male breast, pancreatic, and stomach cancer; male BRCA2 PV carriers had also an increased prostate cancer risk. The authors did not observe increased risks for other cancers, lung cancer in particular. Indeed, overall lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Although we did not observe an overall association with lung cancer risk for either BRCA1 or BRCA2 PV carriers, Fallet et al 1 suggested that the role of BRCA2 PVs in lung cancer should remain open for discussion. We agree with Fallet et al 1 that additional data are required to clarify these associations. Here, we would like to highlight a few methodological considerations in interpreting the results.…”
contrasting
confidence: 92%
See 3 more Smart Citations
“…Although we did not observe an overall association with lung cancer risk for either BRCA1 or BRCA2 PV carriers, Fallet et al 1 suggested that the role of BRCA2 PVs in lung cancer should remain open for discussion. We agree with Fallet et al 1 that additional data are required to clarify these associations. Here, we would like to highlight a few methodological considerations in interpreting the results.…”
contrasting
confidence: 92%
“…Fallet et al 1 also indicated that our analysis included one of the lowest percentages of families in the lung cancer analysis. As mentioned in our study, we excluded any study groups in which underreporting was likely in cancer-specific analyses.…”
mentioning
confidence: 79%
See 2 more Smart Citations